Analysis of Underachiever Students' Mathematical Problem-Solving Ability on The Topic Circle Viewed from Adversity Quotient - Miftahul Jannah; Lukman El Hakim; Anny Sovia (Urogram Studi Pendidikan Matematika, Universitas IVET, 2023)
This study aims to: (1) Know the mathematical problem-solving abilities of underachiever students, (2) Adversity Quotient profiles of underachiever students, and (3) The relationship between Adversity Quotient and mathematical problem-solving abilities of underachiever students. This research is a qualitative research type underachiever case study. The research subjects were 6 underachiever students in 2nd grade at SMA Negeri 6 Bogor and SMA Negeri 1 Babakan Madang. The instruments used in this research were the ARP (Adversity Response Profile) questionnaire and a mathematical problem-solving ability test. Data analysis in this study aims to determine the Adversity Quotient profile using Stolz's theory and mathematical problem-solving abilities based on Polya's steps. The results showed that underachiever students had Camper and Quitter type of Adversity Quotient profiles. Underachiever students with a Camper profile have pretty good mathematical problem-solving abilities. Meanwhile, students who had Quitter profiles have very less good mathematical problem-solving skills. Keywords: problem-solving, underachiever, adversity quotient.